Database coverage in the accounting information system course in Malaysia - Selamat, Mohamad Hisyam; Abdullah, Akilah; Ahmad, Saudah (2000)
This paper reports the results of a survey that examines the extent of coverage of database management systems concept and topics in the undergraduate accounting information systems (AIS) course in Malaysian universities. Broad area surveyed are basic database terminology, database models, designing and optimizing a database, security and control of database systems, and implementation, administration and evaluation of database management systems. Bloom's taxonomy (Bloom, 1956) is used to asses the level of coverage of each topic.The results show that despite the 1986 recommendations of the AAA Committee on Contemporary Approaches to Teaching AIS and recent changes in the accounting profession, it appears that large numbers of Malaysian universities are not covering fundamental concepts and topics in the area of database management systems.On the other hand, the level of coverage is relatively high among those universities which incorporate database concepts and topics into their AIS courses where more than 60 percent of the items are covered at the analysis level and above.This trend seem to be parallel with the growth of information technology and increasing importance of database tools and techniques in practise.